LEGAL CONSEQUENCES OF A DECLARATION OF BANKRUPTCY AGAINST A LIMITED LIABILITY COMPANY ACCORDING TO THE BANKRUPTCY LAW - Anggraini Saputri, Devi (DE'RECHTSSTAAT, 2024)
It is not uncommon to hear about limited companies being declared bankrupt. The imposition of bankruptcy of a limited company is actually not the bankruptcy of the management, but the bankruptcy of the limited company itself, even though it arises which is usually caused by the negligence of the managers in the limited company. The purpose of this study is to determine the legal consequences of the bankruptcy of a limited company. The research method used in this writing is normative juridical which explains that the creditor can demand the dissolution of the limited company if there has been a reading of a bankruptcy order, only because the limited company is unable to pay its debts or the company's assets after being declared bankrupt. The results of the study indicate that the directors can be held liable civilly and criminally for the bankruptcy of a limited company. Civil liability can be in the form of joint and several liability for the losses of a limited company if the bankruptcy is caused by the negligence and negligence of the directors and the company's assets are insufficient to cover the losses arising from the bankruptcy. Criminal liability in the form of imprisonment, in addition to other obligations in the form of confiscation according to bankruptcy law, while the consequences of bankruptcy of a limited liability company are the termination of the company's business activities by creditors and guardians, or by the district court in the form of dissolution by request of creditors on the grounds that the company has failed to pay its debts after being declared bankrupt or the company's assets are insufficient to pay all its debts after the bankruptcy statement is revoked.